Leaf beetle Phyllotreta striolata (Coleoptera: Chrysomelidae): Biology and infestation on Chinese flowering cabbage Brassica rapa var. parachinensis in Bogor, West Java, Indonesia - DIAN AGUNG SANORA LAIA; NINA MARYANA; I WAYAN WINASA (Society for Indonesian Biodiversity, 2024)
Abstract. Laia DAS, Maryana N, Winasa IW. 2024. Leaf beetle Phyllotreta striolata (Coleoptera: Chrysomelidae): Biology and infestation on Chinese flowering cabbage Brassica rapa var. parachinensis in Bogor, West Java, Indonesia. Biodiversitas 25: 3099-3105. Chinese flowering cabbage (Brassica rapa var. parachinensis L.) holds significant economic value and provides essential nutrition. Bogor District, a primary region for vegetable production in Indonesia, faces a severe issue due to the leaf beetle Phyllotreta striolata Fabricius 1803 infestation on Chinese flowering cabbage plants. However, research on this pest in Indonesia is still limited. Observations on the biological aspects of P. striolata involved collecting and identifying adult P. striolata from Chinese flowering cabbage fields, along with biological observations focusing on the beetle's morphology and developmental stages. Population calculations of adult beetles and evaluation of P. striolata infestation intensity on Chinese flowering cabbage plants were conducted in four sub-districts in Bogor District. The average life cycle of this beetle was 27.15 days. The study revealed that the adult stage lasted an average of 119.10 days, with an average preoviposition period of 3.08 days. Adult populations tended to decrease with the age of Chinese flowering cabbage plants due to environmental factors and food source availability. Infestation intensity varied across locations, with Leuwimalang showing the lowest intensity (23.56%) and Laladon the highest (48.76%). These differences suggest that the environment in Leuwimalang may support the resistance of Chinese flowering cabbage plants to leaf pest attacks.